EFFECT OF CADMIUM IONS ON THE GERMINATION OF KARELIAN BIRCH AND SILVER BIRCH SEEDS - Lidia Vetchinnikova; Alexander Titov (Proceedings of the Karelian Research Centre of the Russian Academy of Sciences, 2020)
The effect of cadmium ions (from 10 –6 to 10 –3 M) on seed germination and early development of seedlings was studied in Karelian birch B. pendula Roth var. carelica (Mercklin) Hämet-Ahti and silver birch Betula pendula Roth. It has been shown that even low concentrations of cadmium reduce the germination energy, germination percentage, hypocotyl and germinal root sizes. The most toxic concentration of cadmium was 10 –3 M, and the suppression of seed germination was less pronounced when the exposure lasted for 3 days vs. 7 days. A longer impact (15 days) of cadmium ions completely inhibited embryo development, and the highest concentration (10 –3 M) proved to be lethal to the seeds. Certain quantitative differences were revealed in the reaction of Karelian birch and silver birch plants to the action of cadmium ions, which obviously reflect the biological distinctions between these forms of birch.